Late-stage changes in the composition of cell walls of maize plants expressing an apoplast targeted, senescence enhanced fungal ferulic acid esterase, and the subsequent effects on tissue saccharification. - Marcia M de O Buanafina; Phillip Morris; Sue Dalton; M Fernanda Buanafina; Yijuan Wang (PLoS ONE)
Using maize plants expressing an apoplast targeted Aspergillus niger ferulic acid esterase (FAEA), with FAEA driven by a Lolium multiflorum senescence enhanced promoter (LmSee1), we extended measurements of FAEA activity to late-stage senescing plants and measured the stability of FAEA activity following stover storage. The impact of FAEA expression on cell wall hydroxycinnamic acid levels and arabinoxylan (AX) cross-links, and on the levels of cell wall sugars, acetyl bromide lignin and sugar release following saccharification by a cocktail of cellulases and xylanases, was assessed during plant development to full leaf senescence. These were determined in both individual internodes and in combined leaves and combined internodes of FAEA expressing and control partner plants. FAEA expression was found to increase with plant growth up to the reproductive stage (R) of development in both stems and leaves but decreased as the leaves entered full senescence at R+ (18-20 d after R) stage. Moreover, FAEA activity was shown to be relatively stable over a six-month period following stover storage at 4°C. This FAEA expression resulted in significantly reduced levels of cell wall ferulates and diferulates in internodes. The internodes of late stage and senescing FAEA-expressing plants exhibited significantly improved saccharification with a cocktail of cellulase and xylanase enzymes at both the R and R+ stages of development.